Public Trust and Governance in Driving Urban-Rural Economic Mobility through Licensing Ease - Hasddin Hasddin; Yusuf Jaya Saputra; Cahyo Wijayanto; Melati Melati; Hasjad Hasjad; Rahmanuddin Tomalili; Jabal Arfah; Kalis Amartani (Research Synergy Foundation, 2025)
Economic mobility between urban and rural areas is essential for regional development, particularly in Southeast Sulawesi. This study investigates the relationship between business licensing in the transportation sector, good governance, and public trust in enhancing economic mobility. Specifically, it examines how the ease of business licensing influences public trust (H1) and good governance (H2), and how public trust mediates the relationship between licensing reforms and governance outcomes (H3). Adopting a quantitative approach within a positivist paradigm, data were collected through surveys targeting stakeholders involved in transportation-sector licensing. The analysis utilized Structural Equation Modeling with the Partial Least Squares method (SEM-PLS) to test causal relationships. Results indicate that streamlined business licensing significantly improves public trust, thereby strengthening good governance practices. Furthermore, public trust serves as a mediating factor, linking licensing reforms to improved governance outcomes, underscoring its importance for effective policy implementation. These findings underscore the strategic role of licensing reforms in reducing bureaucratic barriers, enhancing transparency, and fostering public confidence—key drivers for urban-rural economic integration. For policymakers, the study highlights that optimizing licensing processes, strengthening governance, and building trust can facilitate investment, improve transportation infrastructure, and accelerate regional economic connectivity. Future research should examine the broader socio-economic implications of licensing system improvements across different sectors and regions to develop more comprehensive strategies for sustainable regional development.